2016
DOI: 10.1113/jp270654
|View full text |Cite
|
Sign up to set email alerts
|

Do antioxidant supplements interfere with skeletal muscle adaptation to exercise training?

Abstract: A popular belief is that reactive oxygen species (ROS) and reactive nitrogen species (RNS) produced during exercise by the mitochondria and other subcellular compartments ubiquitously cause skeletal muscle damage, fatigue and impair recovery. However, the importance of ROS and RNS as signals in the cellular adaptation process to stress is now evident. In an effort to combat the perceived deleterious effects of ROS and RNS it has become common practice for active individuals to ingest supplements with antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 78 publications
(205 reference statements)
6
194
0
2
Order By: Relevance
“…Since then, although not unambiguously, several studies have reported that supplementing with high doses of single antioxidants may be counterproductive . A growing body of evidence suggests that a transient increase in RONS is a key signal that initiates the adaptive response to training . Consequently, the use of high‐dose antioxidant supplements may weaken this signal.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, although not unambiguously, several studies have reported that supplementing with high doses of single antioxidants may be counterproductive . A growing body of evidence suggests that a transient increase in RONS is a key signal that initiates the adaptive response to training . Consequently, the use of high‐dose antioxidant supplements may weaken this signal.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, PLFFD in muscle of wild-type mice and recreationally active humans was accompanied by RyR1 modification, which can elevate baseline [Ca 2þ ] i , and thereby trigger mitochondrial biogenesis and other beneficial adaptations Place et al 2015). Thus, ROS/RNS-induced modifications in RyR1 structure and function offer a mechanism as to why treatment with antioxidants hamper the beneficial effects of endurance training (Gomez-Cabrera et al 2008;Ristow et al 2009;Paulsen et al 2014;Merry and Ristow 2016). However, RyR1 modification can be a doubleedged sword and severe modifications, for example, a major RyR1 depletion of the associated stabilizing protein FKBP12, have been linked to muscle weakness after strenuous contractile activity (Aydin et al 2008;Bellinger et al 2008b), during aging (Andersson et al 2011), or in various pathological conditions (Bellinger et al 2008a;Waning et al 2015).…”
Section: The Primary Ros In Cells Are the Superoxide Anion (O 2 †2mentioning
confidence: 95%
“…In particular, acute supplementation (e.g., prior to an exercise session) may exert favorable ergogenic effects (e.g., enhanced performance and delayed muscle fatigue) [62,63,64]. On the other, chronic supplementation with antioxidants, contrary to the habitual practice, is increasingly acknowledged as detrimental compromising both redox and exercise adaptations [65,66].…”
Section: The Temporal Pattern Of Antioxidant Administrationmentioning
confidence: 97%